2019
DOI: 10.9734/ajrb/2019/v5i330091
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Hypolipidemic and Angiotensin Converting Enzyme Inhibitory Effects of Flavonoid-rich Fraction of Hyphaene thebaica (Doum Palm) Fruits on Fat-fed Obese Wistar Rats

Abstract: Aims: This study investigated the antioxidant, hypolipidemic and angiotensin converting enzyme (ACE) inhibitory effects of flavonoid-rich fraction of H. thebaica on fat-fed obese wistar rats. Study Design: Twenty-five rats were divided into 5 groups of 5 rats each: Control (standard diet, untreated), Obese control (Fat-fed, untreated), Standard control (Fat-fed, treated with 70 mg/kg Atorvastatin), Groups 4 and 5 (Fat-fed, treated with 100 and 250 mg kg-1 flavonoid-rich fraction, respectively). The rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
4
3
0
Order By: Relevance
“…However, treatment with H. thebaica extracts significantly (P < 0.05) decreased the total lipids, triglyceride, total cholesterol, and LDL of all treated groups as compared to the diabetic rats. Abdulazeez et al, (2019) and Bayad (2016), reported results similar to the present study.…”
Section: Resultssupporting
confidence: 92%
“…However, treatment with H. thebaica extracts significantly (P < 0.05) decreased the total lipids, triglyceride, total cholesterol, and LDL of all treated groups as compared to the diabetic rats. Abdulazeez et al, (2019) and Bayad (2016), reported results similar to the present study.…”
Section: Resultssupporting
confidence: 92%
“…As well as the aqueous extract of Hyphaene thebaica which possesses an antioxidant activity due to its substantial amount of water-soluble phenolic content. These results are in agreement with other studies [34] [38].…”
Section: Antioxidant Enzymes Activity In Plasmasupporting
confidence: 94%
“…Insulin can activate are act as glucosidase inhibitors, reducing the lipoprotein lipase, the enzyme lipoprotein solver. These results are in agreement with other studies [32] [34].…”
Section: Blood Lipid Profilesupporting
confidence: 94%
See 1 more Smart Citation
“…17 HFD was prepared daily and rats were given this diet for 6 weeks until they become obese. 18 Rat obesity was judged indirectly by comparing the weight of HFD-fed to ND-fed rats, and the extract of E. japonica was given for another 6 weeks.…”
Section: Animalsmentioning
confidence: 99%